KONTEKSTUALISASI TEOLOGI HINDU TEKS Ä€DIPARWA DI UPT TAMAN BUDAYA PROVINSI BALI - Subrahmaniam Saitya, Ida Bagus; Suarka, I Nyoman; Duija, I Nengah (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Ä€diparwa is an early part of aá¹£á¹adaÅ›aparwa that forms the MahÄbhÄrata, consisting of 2 (two) separate sections. The first part presents the framework of the BhÄrata epic, the story of the sacrificial rites on the orders of King Janamejaya in order to destroy the dragons because King Pariká¹£it who was the father of King Janamejaya was killed by the Taksaka dragon. The second part, contains the genealogy of the PÄá¹‡á¸awa and Korawa, their birth and youth to Arjuna's marriage to SubhadrÄ. In the Ä€diparwa text there is also another story, the story of the rotation of Mount Mandara, which fighting between the gods and the daitya. In the story of the rotation of Mount Mandara transformed into the form of existing buildings at UPT Taman Budaya Provinsi Bali.